Effects of Ultrasonic Power and Intensity of Mechanical Agitation on Pretreatment of a Gold-Bearing Arsenopyrite - HONG, Won Chol; KIM, Ye Yong; KWON, Chang Dok; SO, Kwang Chol (Archives of Acoustics, 2024)
In this paper, the effects of an ultrasonic power and the intensity of mechanical agitation for pulp on alkaline pretreatment of gold-bearing arsenopyrite were investigated. The effect of pulp temperature on leaching efficiency in alkaline pretreatment of arsenopyrite was investigated under ultrasound and non-ultrasound conditions. Pre-treatment was followed by gold leaching tests with a cyanide solution. Compared with the nonultrasound condition at the temperature of 60 °C, arsenic extraction and gold extraction was increased 20 %, 14.4 %, respectively, in the presence of ultrasound at ambient temperature. The characteristics of the ultrasonic power level as a function of the intensity of mechanical agitation were evaluated by a numerical simulation with CFD software – Ansys Fluent. The simulation results demonstrated that the stronger intensity of mechanical agitation, the lower ultrasonic power level. These results were proved through leaching experiments at different rotation speeds of impeller and ultrasonic powers.The study results demonstrate that the ultrasound is an effective factor for pretreatment of gold bearing arsenopyrite and gold extraction is related to an ultrasonic power and the intensity of mechanical agitation.